Empirical Legal Research Methods: Applications in Legal Research in Indonesia - Retno Widyani; Li Wei; Wang Jun (Yayasan Adra Karima Hubbi, 2025)
Background. Empirical legal research methods have gained increasing significance in legal scholarship, offering insights into the real-world application and outcomes of laws. In Indonesia, the use of these methods remains relatively underexplored despite the growing need for evidence-based policy and legal reforms. Legal research in Indonesia has traditionally relied on doctrinal methods, but empirical approaches have the potential to enhance the understanding of how legal systems function in practice and how laws impact society. Objective. This study aims to explore the applications of empirical legal research methods in legal research in Indonesia. The research focuses on examining how these methods can be effectively implemented in the context of Indonesian legal research to address pressing legal issues and improve the legal system's overall effectiveness. Method. A qualitative research design was employed, combining a review of existing literature, case studies, and interviews with legal scholars, practitioners, and policymakers. The study also analyzed existing empirical research on legal issues in Indonesia to identify current trends and gaps in research. Results. The findings suggest that empirical methods, such as surveys, interviews, and case studies, are increasingly being adopted in Indonesian legal research, though challenges remain in terms of resources, training, and institutional support. Conclusion. Empirical legal research holds significant potential for advancing legal scholarship in Indonesia. There is a need for greater integration of these methods to enhance the quality and relevance of legal research and inform legal reforms.